THE INFLUENCE OF DIGITALIZATION IN THE RISE OF BULLYING CASES IN COMMUNITY ENVIRONMENT - Mulyadi; Farandy, Farrel; Nusa Prawira, Rio; Tsuraya Rasmawan, Ariq; Ahmad Rizal, Sultan; Ahmad Ardhika, Wafiy; Halky Syahrir, Fabhian (Fakultas Hukum Universitas Djuanda, 2024)
In the era of digitalization, of course technology plays a big role in making it easier for people to carry out their activities by providing fast access to information, but behind the convenience provided by electronic media, there is a negative side as a result of using electronic media in an unwise way, one of which is behavior. Bullying is someone's aggressive treatment of another person by insulting, threatening and intimidating, causing psychological disorders to the victim. In the era of digitalization, this bullying case also extends to using electronic media for the perpetrator to insult and hate someone via social media or what is called cyberbullying. This research uses a literature study method, carried out by reading, collecting, reviewing various books, related journals, laws and other writings. In this digital era, bullying is no longer limited to direct physical interactions, but also reaches the virtual realm. Social media, instant messaging platforms, and online forums have become a means for bullies to spread content that demeans, insults, and intimidates their victims. Therefore, in the era of digitalization, as a good user of electronic media, you should be able to behave well both in real life and on social media.